Green Finance, Capital Structure, and Firm Value: The Mediation Role of Sustainability Disclosure in Indonesia - Sukma Febrianti; Mustaruddin Mustaruddin; Wendy Wendy (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
ABSTRACT Background of study: The growing global concern regarding environmental sustainability has encouraged companies to integrate sustainable finance and transparency practices into corporate strategies. Green Finance and Sustainability Disclosure have become important instruments in supporting long-term corporate value creation. Aims and scope of paper: This study aims to examine the effect of Green Finance and Capital Structure on Firm Value with Sustainability Disclosure acting as a mediating variable. The research focuses on understanding how sustainable financial practices contribute to corporate valuation. Methods: This study aims to examine the effect of Green Finance and Capital Structure on Firm Value with Sustainability Disclosure acting as a mediating variable. The research focuses on understanding how sustainable financial practices contribute to corporate valuation. Result: The findings indicate that Green Finance has a positive and significant effect on Firm Value and Sustainability Disclosure. Capital Structure does not directly influence Firm Value but significantly affects Sustainability Disclosure. Furthermore, Sustainability Disclosure partially mediates the relationship between Green Finance and Firm Value. Conclusion: The results suggest that Green Finance enhances Firm Value both directly and indirectly through improved Sustainability Disclosure. Integrating sustainable financing with transparent sustainability reporting is essential for strengthening investor confidence and supporting long-term corporate performance.